Heavy metal contamination status in soil-plant system in the Upper Mersey Estuarine Floodplain, Northwest England. (September 2019) - Enya, Osim; Lin, Chuxia; Qin, Junhao
Abstract: Globally, soil contamination by heavy metals is common in estuarine floodplains. A study was conducted to assess heavy metal contamination in the soil-plant system in Mersey estuarine floodplain, North West England. Representative composite soil samples and plant samples were collected from nine identified land use types across the study area. Various fraction of heavy metals in soils and plant tissue-borne heavy metals were determined. The results show that the study area has elevated concentrations of As, Cr, Cu, Pb and Zn. Heavy metal concentration in soils was generally higher in the lowlying areas than in the upland portions. There was a trend that concentration of heavy metals increased with increasing depth due to de-industrialisation in the upper catchment. The soil contamination resulted in elevated concentration of heavy metals in the grazed plants, which could pose a risk to wild animals, grazing animals and people who consume the grazing animal meat. Highlights: Heavy metal status in soil-plant system in a historically contaminated estuary Heavy metals in soils tended to be higher in lowlands than in highlands Concentration of heavy metals decreased upward due to de-industrialisation Marked uptake of heavy metals by grazed saltmarsh plants Grazing restriction needed to minimise health risk from contaminated soils